A Plymouth Brethren controversy revisited Henry Young and A plea for the honour of Christ - Braga, Stuart (Beecroft, NSW Stuart Braga, 2003)
Includes bibliographical references, index and photographs.
Donated by the author.
Keywords: Brethren movement -- controversial literature; Brethren movement -- Australasia -- history; Brethren movement -- doctrines